FISH FAUNA AND POPULATION DYNAMICS OF ECONOMICALLY IMPORTANT FISH SPECIES OF MANMADE FRESHWATER RESERVOIR - AHMAD, I; QAYYUM, M; HAYAT, S; AHMAD, F (Biological and Clinical Sciences Research Journal, 2022)
Chashma reservoir is located at latitude of Nº 32'26.110 and longitude of E° 71'25.571 and is constructed on the river Indus at District Mianwali on Dera Ismail Khan Road in the province of Punjab, Pakistan. It is the third largest multi-purpose reservoir in Pakistan and covers a surface area of 360 Km². It is used for flood control, irrigation, power generation and fish production. Its fish biodiversity was studied during a period of twenty four months from September 2013 to September 2015. Various fishing gears like hand nets, mosquito nets, rod and line, cast nets, drag nets and gill nets etc. were employed for sample collection. Total 74 numbers of fish species distributed over 9 orders, 21 families and 54 genera were recorded. Population dynamics of commercial fish specieswas also studied. Their numbers and biomass in the fish catch were recorded. Labeo gonius is the most prevalent species and found 50% in number and 37.34% in biomass in the total harvest whereas Wallago attu is the most commercial fish species which represent 5.37 % in number and 18% by weight in the total fish catch. Fish species are classified as common (C), not common (NC), rare (R), and very rare (VR) based on how frequently they appeared in the samples. Species utilized for aquaculture are marked as (CU) and the exotic species are represented as (E). This reservoir hosts around 39% of Pakistan's entire freshwater fish biodiversity.